Silicon-carbon negative electrode material, preparation method thereof, negative electrode sheet and lithium ion battery

CN122950428APending Publication Date: 2026-10-20SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611070100.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]本申请的主要目的在于提供一种硅碳负极材料及其制备方法、负极片及锂离子电池,以解决现有技术中硅碳负极材料的界面阻抗高及其在匀浆过程中产气量大的问题,以及由此导致的锂离子电池功率性能和循环性能较差的问题

Benefits of technology

[0027]应用本申请的技术方案,提供了一种硅碳负极材料,设置在内核表面的含氟碳层具有优异的化学稳定性和致密性,能够起到物理阻隔的作用,隔绝水分子与硅的直接接触;氟元素的引入能够降低含氟碳层的表面能,进一步降低水分子在硅碳负极材料表面的润湿和渗透能力,从而形成有效的疏水屏障,抑制硅与水中的氢氧根离子(OH-)反应,降低氢气的生成量。同时,氟原子的高电负性能够改善含氟碳层的电子结构,降低界面电阻,并提供额外的活性位点,有助于锂离子的快速嵌入和脱出,从而有效提高硅碳负极材料的锂离子扩散速率。在内核中的多孔碳骨架表面及其孔道内设置碳层,能够有效减少硅基材料在复合多孔碳基体孔道内的暴露面积,从而减少硅与水分子的接触路径,进一步降低匀浆过程中的产气量。复合多孔碳基体的多孔结构还为硅基材料在充放电循环中的体积膨胀提供了充足的缓冲空间,能够有效提高硅碳负极材料的结构稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

This application provides a silicon-carbon anode material, its preparation method, an anode sheet, and a lithium-ion battery. The silicon-carbon anode material includes a core and a fluorinated carbon layer disposed on the surface of the core. The core includes a composite porous carbon matrix and a silicon-based material deposited on the surface and within the pores of the composite porous carbon matrix. The composite porous carbon matrix includes a porous carbon framework and a carbon layer disposed on the surface and within the pores of the porous carbon framework. By constructing a porous silicon-carbon core structure coated with a fluorinated carbon layer, this application achieves a dual improvement in the processing performance and electrochemical performance of the silicon-carbon anode material. It effectively reduces the gas generation during the homogenization process of the silicon-carbon anode material, improves the safety and coating performance during the anode sheet production process, and significantly improves the electrochemical performance of the anode sheet prepared from it. Applying the above-mentioned silicon-carbon anode material to lithium-ion batteries can effectively improve the power performance and cycle stability of lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion battery technology, and more specifically, to a silicon-carbon anode material and its preparation method, an anode sheet, and a lithium-ion battery. Background Technology

[0002] Silicon-carbon anode materials are considered a novel high-performance lithium-ion battery anode material due to their advantages such as high specific capacity, good safety performance, wide availability of raw materials, and low cost. However, in aqueous slurry systems, the active silicon remaining on the surface of silicon-carbon anode materials (i.e., surface-floating silicon) easily reacts with hydroxide ions (OH-) in water, producing a large amount of hydrogen gas. Severe gas production leads to decreased stability of the anode slurry, affecting its coating performance. During the coating process and subsequent processing, gas escape can easily form structural defects such as pinholes and cracks, resulting in increased internal resistance and deteriorated cycle performance. Simultaneously, the accumulation of large amounts of hydrogen inside the battery poses an explosion risk, severely restricting the large-scale production and safe application of silicon-carbon anode materials.

[0003] To alleviate the above problems, the industry currently uses chemical vapor deposition (CVD) to coat the surface of silicon-carbon materials with a carbon layer, aiming to reduce the direct contact between the floating silicon on the surface of silicon-carbon materials and water through physical barriers, thereby suppressing gas generation. However, the existing CVD process has the following limitations: (1) Traditional CVD processes are usually carried out at low temperatures (<600°C), resulting in poor density of the carbon layer, micropores, cracks and uneven coverage, which leads to the inability to completely block the penetration of water molecules, and residual gas generation still exists significantly; (2) The existing single carbon coating mainly plays a physical barrier role and lacks the ability to improve lithium-ion transport dynamics, and has limited improvement on the electrochemical performance of silicon-carbon anode materials (such as lithium-ion diffusion rate and interface impedance).

[0004] In summary, a silicon-carbon anode material and its preparation method have been researched and developed to reduce the gas production of silicon-carbon anode material during homogenization without changing the existing aqueous slurry preparation process, while improving the electrochemical performance of silicon-carbon anode material. This is of great significance for improving the stability of silicon-carbon anode material in aqueous homogenization system, as well as improving the power performance and cycle performance of lithium-ion batteries. Summary of the Invention

[0005] The main objective of this application is to provide a silicon-carbon anode material and its preparation method, anode sheet and lithium-ion battery, so as to solve the problems of high interfacial impedance of silicon-carbon anode materials and large gas generation during homogenization in the prior art, and the resulting poor power performance and cycle performance of lithium-ion batteries.

[0006] To achieve the above objectives, this application provides a silicon-carbon anode material, which includes a core and a fluorinated carbon layer disposed on the surface of the core; the core includes a composite porous carbon matrix and a silicon-based material deposited on the surface and within the pores of the composite porous carbon matrix, and the composite porous carbon matrix includes a porous carbon skeleton and a carbon layer disposed on the surface and within the pores of the porous carbon skeleton.

[0007] Furthermore, the D of silicon-carbon anode materials 50 It ranges from 4 to 12 μm.

[0008] Furthermore, in the silicon-carbon anode material, the carbon content is 40-60 wt%, and the silicon content is 40-60 wt%.

[0009] Furthermore, the weight ratio of the core to the fluorocarbon layer is 100:(0.4-8).

[0010] Furthermore, the thickness of the fluorocarbon layer is 3–20 nm; preferably, the fluorine content in the fluorocarbon layer accounts for 0.2–4 wt% of the weight of the silicon-carbon anode material.

[0011] Furthermore, the kernel's D 50 It ranges from 4 to 12 μm.

[0012] Furthermore, the weight ratio of the composite porous carbon matrix to the silicon-based material is 1:(0.67~1.5).

[0013] Furthermore, in the composite porous carbon matrix, the weight ratio of the porous carbon framework to the carbon layer is 100:(2-5); preferably, the thickness of the carbon layer is 1-5 nm.

[0014] To achieve the above objectives, another aspect of this application provides a method for preparing the silicon-carbon anode material provided in this application. The method includes: step S1, providing a porous carbon framework, and performing a first vapor phase deposition treatment on the porous carbon framework in an atmosphere containing a carbon source to obtain a composite porous carbon matrix; step S2, performing a second vapor phase deposition treatment on the composite porous carbon matrix in an atmosphere containing a silicon source to obtain a core; step S3, performing a third vapor phase deposition treatment on the core in a coating gas atmosphere to form a fluorinated carbon layer on the surface of the core to obtain the silicon-carbon anode material; wherein the coating gas is selected from fluorinated organic compound gas or a combination of fluorinated organic compound gas and alkane gas.

[0015] Furthermore, in step S3, the ratio of the volume of the encapsulated gas introduced to the weight of the core is (400~1000) L:1kg.

[0016] Furthermore, the coating gas is a combination of fluorinated organic compound gas and alkane gas, and the weight ratio of fluorinated organic compound gas to alkane gas is (1-2):(1-2).

[0017] Furthermore, the fluorinated organic compound gas is selected from one or more of tetrafluoromethane, nitrogen trifluoride, Freon, polyvinylidene fluoride, perfluoropolyether, tetrafluoroethylene, trifluorochloroethylene, perfluorocyclobutane, and fluoroethylene carbonate.

[0018] Furthermore, the alkane gas is selected from one or more of C1 to C4 alkane gases; preferably, the alkane gas is selected from one or more of methane, acetylene, and natural gas.

[0019] Furthermore, the temperature of the third vapor deposition process is 650–800°C, and the time is 12–48 h; preferably, the temperature of the third vapor deposition process is 750–800°C.

[0020] Furthermore, step S3 also includes a heat preservation treatment performed after the third vapor deposition treatment is completed; preferably, the temperature of the heat preservation treatment is 650-800°C and the time is 1-2 hours; more preferably, the temperature of the heat preservation treatment is the same as the temperature of the third vapor deposition treatment.

[0021] Further, in step S1, the ratio of the volume of carbon source introduced to the weight of the porous carbon skeleton is (10-50) L:1kg; preferably, the carbon source is selected from one or more of methane, acetylene and natural gas; preferably, the material used to prepare the porous carbon skeleton is selected from one or more of resin-based carbon materials, biomass-based carbon materials and coal-based carbon materials.

[0022] Furthermore, the temperature for the first vapor deposition is 500–600 °C, and the time is 2–12 h.

[0023] Furthermore, in step S2, the ratio of the volume of silicon source introduced to the weight of the composite porous carbon matrix is ​​(500~1000) L:1kg.

[0024] Furthermore, the temperature for the second vapor deposition is 400–600 °C, and the time is 8–24 h.

[0025] Another aspect of this application provides a negative electrode sheet, including a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer includes the silicon-carbon negative electrode material provided in this application.

[0026] A fourth aspect of this application also provides a lithium-ion battery, including a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, wherein the negative electrode is the aforementioned negative electrode provided in this application.

[0027] This application provides a silicon-carbon anode material. The fluorinated carbon layer on the core surface possesses excellent chemical stability and density, acting as a physical barrier to prevent direct contact between water molecules and silicon. The introduction of fluorine reduces the surface energy of the fluorinated carbon layer, further decreasing the wetting and penetration ability of water molecules on the surface of the silicon-carbon anode material, thus forming an effective hydrophobic barrier and inhibiting the reaction of silicon with hydroxide ions (OH-) in water. - The reaction reduces hydrogen production. Simultaneously, the high electronegativity of fluorine atoms improves the electronic structure of the fluorinated carbon layer, reduces interfacial resistance, and provides additional active sites, facilitating rapid lithium-ion insertion and extraction, thereby effectively increasing the lithium-ion diffusion rate of the silicon-carbon anode material. The carbon layer on the surface and within the pores of the porous carbon framework in the core effectively reduces the exposed area of ​​silicon-based materials within the pores of the composite porous carbon matrix, thus reducing the contact path between silicon and water molecules and further reducing gas production during homogenization. The porous structure of the composite porous carbon matrix also provides ample buffer space for the volume expansion of silicon-based materials during charge-discharge cycles, effectively improving the structural stability of the silicon-carbon anode material.

[0028] In summary, this application achieves a dual improvement in the processing performance and electrochemical performance of silicon-carbon anode materials by constructing a porous silicon-carbon core structure coated with a fluorinated carbon layer. Specifically, on the one hand, it effectively reduces the gas generation of silicon-carbon anode materials during the homogenization process, improving the safety and coating performance of the anode sheet production process; on the other hand, it increases the lithium-ion diffusion rate of silicon-carbon anode materials, thus improving the electrochemical performance of the anode sheets made from them. Applying the silicon-carbon anode material provided in this application to lithium-ion batteries can effectively improve the power performance and cycle stability of lithium-ion batteries. Attached Figure Description

[0029] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings:

[0030] Figure 1 The SEM image of the silicon-carbon anode material prepared in Example 1 of this application is shown. Detailed Implementation

[0031] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present application will now be described in detail with reference to the embodiments.

[0032] As described in the background section, existing silicon-carbon anode materials suffer from poor interface stability and high gas generation during homogenization, resulting in poor power performance and cycle performance of lithium-ion batteries. To address these technical problems, this application provides a silicon-carbon anode material comprising a core and a fluorinated carbon layer disposed on the surface of the core. The core comprises a composite porous carbon matrix and a silicon-based material deposited on the surface and within the pores of the composite porous carbon matrix. The composite porous carbon matrix comprises a porous carbon framework and a carbon layer disposed on the surface and within the pores of the porous carbon framework.

[0033] In the silicon-carbon anode material provided in this application, the fluorinated carbon layer disposed on the core surface has excellent chemical stability and density, which can play a physical barrier role, preventing water molecules from directly contacting silicon. The introduction of fluorine can reduce the surface energy of the fluorinated carbon layer, further reducing the wetting and penetration ability of water molecules on the surface of the silicon-carbon anode material, thereby forming an effective hydrophobic barrier and inhibiting the reaction of silicon with hydroxide ions (OH-) in water. - The reaction reduces hydrogen production. Simultaneously, the high electronegativity of fluorine atoms improves the electronic structure of the fluorinated carbon layer, reduces interfacial resistance, and provides additional active sites, facilitating rapid lithium-ion insertion and extraction, thereby effectively increasing the lithium-ion diffusion rate of the silicon-carbon anode material. The carbon layer on the surface and within the pores of the porous carbon framework in the core effectively reduces the exposed area of ​​silicon-based materials within the pores of the composite porous carbon matrix, thus reducing the contact path between silicon and water molecules and further reducing gas production during homogenization. The porous structure of the composite porous carbon matrix also provides ample buffer space for the volume expansion of silicon-based materials during charge-discharge cycles, effectively improving the structural stability of the silicon-carbon anode material.

[0034] It should be noted that in the aqueous slurry preparation process of the silicon-carbon anode material provided in this application, the reaction equation between water and silicon in the slurry is: Si + 4H2O → H4SiO4 + 2H2 (g).

[0035] In summary, this application achieves a dual improvement in the processing performance and electrochemical performance of silicon-carbon anode materials by constructing a porous silicon-carbon core structure coated with a fluorinated carbon layer. Specifically, on the one hand, it effectively reduces the gas generation of silicon-carbon anode materials during the homogenization process, improving the safety and coating performance of the anode sheet production process; on the other hand, it increases the lithium-ion diffusion rate of silicon-carbon anode materials, thus improving the electrochemical performance of the anode sheets made from them. Applying the silicon-carbon anode material provided in this application to lithium-ion batteries can effectively improve the power performance and cycle stability of lithium-ion batteries.

[0036] In a preferred embodiment, the silicon-carbon anode material D 50The diameter is 4–12 μm. Compared to other ranges, the D of silicon-carbon anode materials is significantly larger. 50 Limiting the process to the above range is beneficial to improving the processability of silicon-carbon anode materials and their stability in aqueous homogenization systems, and also to improving the compaction density of the anode sheets made from them.

[0037] In order to synergistically improve the structural stability and specific capacity of silicon-carbon anode materials, in a preferred embodiment, the content of carbon in silicon-carbon anode materials is 40-60 wt%, and the content of silicon is 40-60 wt%.

[0038] In a preferred embodiment, the weight ratio of the core to the fluorocarbon layer is 100:(0.4-8). Compared to other ranges, limiting the weight ratio of the core to the fluorocarbon layer to the above range is beneficial for the fluorocarbon layer to be more completely and continuously coated on the surface of the core, better suppressing the side reactions between water molecules and silicon, reducing the gas generation of the silicon-carbon anode material during the homogenization process, and also helping to reduce the interfacial resistance of the silicon-carbon anode material and increase the lithium-ion diffusion rate, thereby improving the power performance and cycle performance of the prepared lithium-ion battery.

[0039] In order to further suppress the side reaction between water molecules and silicon, reduce the gas production of silicon-carbon anode material during homogenization, and further reduce the interfacial resistance of silicon-carbon anode material and improve the lithium ion diffusion rate, in a preferred embodiment, the thickness of the fluorocarbon layer is 3-20 nm.

[0040] In a preferred embodiment, the fluorine content in the fluorocarbon layer accounts for 0.2–4 wt% of the weight of the silicon-carbon anode material. Compared to other ranges, limiting the fluorine content in the fluorocarbon layer to the above range is beneficial to improving the hydrophobicity of the fluorocarbon layer, isolating water molecules from contact with silicon, further reducing the gas generation of the silicon-carbon anode material during the homogenization process, and also helping to reduce the interfacial resistance of the silicon-carbon anode material and improve the lithium-ion diffusion rate.

[0041] To further improve the dispersibility and coating uniformity of silicon-carbon anode materials during slurry preparation and coating processes, in a preferred embodiment, the core's D... 50 It ranges from 4 to 12 μm.

[0042] In a preferred embodiment, the weight ratio of the composite porous carbon matrix to the silicon-based material is 1:(0.67 to 1.5). The weight ratio of the composite porous carbon matrix to the silicon-based material includes, but is not limited to, the range described above. Limiting it to this range helps to balance the structural stability and specific capacity of the silicon-carbon anode material, thereby improving the power performance and cycle stability of the resulting lithium-ion battery.

[0043] To further improve the structural and interfacial stability of silicon-carbon anode materials, in a preferred embodiment, the weight ratio of porous carbon framework to carbon layer in the composite porous carbon matrix is ​​100:(2-5).

[0044] In a preferred embodiment, the thickness of the carbon layer is 1–5 nm. The thickness of the carbon layer includes, but is not limited to, the above range. Limiting it to the above range is beneficial to improving the structural and interfacial stability of the silicon-carbon anode material, as well as the conductivity of the silicon-carbon anode material, thereby improving the power performance and cycle stability of the prepared lithium-ion battery.

[0045] The second aspect of this application also provides a method for preparing the silicon-carbon anode material provided in this application. The method includes: step S1, providing a porous carbon framework, and performing a first vapor phase deposition treatment on the porous carbon framework in an atmosphere containing a carbon source to obtain a composite porous carbon matrix; step S2, performing a second vapor phase deposition treatment on the composite porous carbon matrix in an atmosphere containing a silicon source to obtain a core; step S3, performing a third vapor phase deposition treatment on the core in a coating gas atmosphere to form a fluorinated carbon layer on the surface of the core to obtain the silicon-carbon anode material; wherein the coating gas is selected from fluorinated organic compound gas or a combination of fluorinated organic compound gas and alkane gas.

[0046] In step S1 of the above preparation method, a first vapor deposition treatment is performed on the porous carbon framework in an atmosphere containing a carbon source to construct a uniform and dense carbon layer on the surface of the porous carbon framework, resulting in a composite porous carbon matrix. This improves the conductivity of the prepared silicon-carbon anode material and effectively reduces the exposed area of ​​silicon-based material within the pores of the composite porous carbon matrix, reducing the contact path between silicon and water molecules and further reducing gas generation during the homogenization process. In step S2, a silicon source is introduced for a second vapor deposition treatment. The porous structure of the composite porous carbon matrix guides the uniform deposition and embedding of silicon-based material to obtain a core, thereby effectively buffering the volume expansion of silicon-based material during charge-discharge cycles, inhibiting pulverization of the silicon-carbon anode material, and improving the structural stability of the anode sheet prepared therefrom. In step S3, a third-phase vapor deposition process is performed using a fluorinated organic compound gas or a mixture of a fluorinated organic compound gas and an alkane gas to form a fluorinated carbon layer on the core surface that has both high chemical stability and good lithium-ion transport performance. On the one hand, this process can suppress the reaction of silicon with hydroxide ions (OH-) in water and reduce the amount of hydrogen generated. On the other hand, the high electronegativity of fluorine atoms can improve the electronic structure of the fluorinated carbon layer, reduce the interfacial resistance, and provide additional active sites, which helps the rapid insertion and extraction of lithium ions and improves the lithium-ion diffusion rate, thereby effectively improving the electrochemical performance of the prepared silicon-carbon anode material.

[0047] In summary, the silicon-carbon anode material prepared by the above-mentioned preparation method provided in this application exhibits good stability and processability in an aqueous homogenization system. It significantly reduces the gas generation of the silicon-carbon anode material during the homogenization process, improves the safety and coating performance of the anode sheet production process, and also has excellent electrochemical performance. It can effectively reduce the interfacial resistance of the anode sheet, thereby improving the power performance and cycle stability of lithium-ion batteries.

[0048] In a preferred embodiment, in step S3, the ratio of the volume of the encapsulated gas introduced to the weight of the core is (400-1000) L:1 kg. Compared to other ranges, limiting the ratio of the volume of the encapsulated gas introduced to the weight of the core within the above range is beneficial for forming a dense, continuous, and appropriately thick fluorocarbon layer, thereby reducing the gas generation of the prepared silicon-carbon anode material during the homogenization process, reducing its interfacial resistance, and increasing the lithium-ion diffusion rate.

[0049] In a preferred embodiment, the coating gas is a combination of a fluorinated organic compound gas and an alkane gas, and the weight ratio of the fluorinated organic compound gas to the alkane gas is (1-2):(1-2). The weight ratio of the fluorinated organic compound gas to the alkane gas includes, but is not limited to, the above range. Limiting it to the above range is beneficial for forming a denser and more stable fluorinated carbon layer, thereby helping to suppress the side reactions between water molecules and silicon, reducing the gas production of the prepared silicon-carbon anode material during the homogenization process, and also helping to improve the electrochemical performance of the prepared silicon-carbon anode material.

[0050] To promote the formation of a more uniform and dense fluorocarbon layer, in a preferred embodiment, the fluorinated organic compound gas includes, but is not limited to, one or more of tetrafluoromethane, nitrogen trifluoride, Freon, polyvinylidene fluoride, perfluoropolyether, tetrafluoroethylene, trifluorochloroethylene, perfluorocyclobutane, and fluoroethylene carbonate.

[0051] In order to promote the formation of a denser and more continuous fluorocarbon layer and further improve the conductivity of the obtained silicon-carbon anode material, in a preferred embodiment, the alkane gas includes, but is not limited to, one or more of C1 to C4 alkane gases; preferably, the alkane gas includes, but is not limited to, one or more of methane, acetylene and natural gas.

[0052] In a preferred embodiment, the temperature of the third vapor deposition treatment is 650–800°C, and the time is 12–48 h. The temperature and time of the third vapor deposition treatment include, but are not limited to, the above ranges. Limiting them to the above ranges is beneficial to improving the efficiency and effect of the third vapor deposition treatment, and is beneficial to forming a more uniform and continuous fluorinated carbon layer. This is beneficial to reducing the amount of gas generated in the homogenization process of the prepared silicon-carbon anode material and improving its electrochemical performance.

[0053] To further improve the efficiency and effectiveness of the third vapor deposition process and promote the formation of a more uniform and continuous fluorocarbon layer, the temperature of the third vapor deposition is preferably 750–800°C.

[0054] In a preferred embodiment, step S3 further includes a heat preservation treatment performed after the third vapor deposition process. Compared to other methods, the above method is beneficial for improving the coating effect of the third vapor deposition process and promoting the formation of a more uniform and continuous fluorocarbon layer.

[0055] To promote the formation of a more uniform and continuous fluorocarbon layer, preferably, the heat preservation treatment temperature is 650-800℃ and the time is 1-2h.

[0056] To further improve the coating effect of the third vapor deposition process and promote the formation of a more uniform and continuous fluorocarbon layer, more preferably, the temperature of the heat preservation process is the same as the temperature of the third vapor deposition process.

[0057] In order to obtain a carbon layer of suitable thickness and further regulate the pore structure of the composite porous carbon matrix, thereby further improving the structural stability and interface stability of the silicon-carbon anode material, in a preferred embodiment, in step S1, the ratio of the volume of carbon source introduced to the weight of the core is (10-50) L:1kg.

[0058] To promote the formation of a more stable carbon layer and further enhance the bonding tightness between the carbon layer and the porous carbon framework, in a preferred embodiment, the carbon source includes, but is not limited to, one or more of methane, acetylene, and natural gas.

[0059] To further improve the structural stability of the prepared silicon-carbon anode material, in a preferred embodiment, the material used to prepare the porous carbon framework includes, but is not limited to, one or more of resin-based carbon materials, biomass-based carbon materials, and coal-based carbon materials. Specifically, the resin-based carbon material can be phenolic resin; the biomass-based carbon material can be coconut shell carbon; and the coal-based carbon material can be pitch. It should be noted that the above-mentioned resin-based carbon materials, biomass-based carbon materials, and coal-based carbon materials are carbonized to obtain a porous carbon framework.

[0060] In a preferred embodiment, the temperature of the first vapor deposition is 500–600°C, and the time is 2–12 hours. The temperature and time of the first vapor deposition process include, but are not limited to, the above ranges. Limiting them to the above ranges is beneficial to improving the efficiency and effect of the first vapor deposition process, promoting the formation of a more uniform and continuous carbon layer, thereby improving the structural stability and interface stability of the prepared silicon-carbon anode material.

[0061] In order to further improve the structural stability and specific capacity of the prepared silicon-carbon anode material, in a preferred embodiment, in step S2, the ratio of the volume of silicon source introduced to the weight of the composite porous carbon matrix is ​​(500~1000) L:1kg.

[0062] The silicon source used in this application may be any type commonly used in the art; for example, the silicon source used in this application may be silane.

[0063] In a preferred embodiment, the temperature for the second vapor deposition is 400–600°C, and the time is 8–24 hours. The temperature and time of the second vapor deposition process include, but are not limited to, the above-mentioned ranges. Limiting them to the above-mentioned ranges is beneficial to improving the efficiency and effect of the second vapor deposition process, promoting the uniform deposition of silicon-based materials, and thus improving the structural stability and specific capacity of the obtained silicon-carbon anode material.

[0064] A third aspect of this application also provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the silicon-carbon negative electrode material provided in this application. This application achieves a dual improvement in the processing performance and electrochemical performance of the silicon-carbon negative electrode material by constructing a porous silicon-carbon core structure coated with a fluorocarbon layer. It effectively reduces the gas generation of the silicon-carbon negative electrode material during the homogenization process, improves the safety and coating performance during the production of the negative electrode sheet, and significantly improves the electrochemical performance of the negative electrode sheet made therefrom. Applying the negative electrode sheet made from the silicon-carbon negative electrode material provided in this application to lithium-ion batteries can effectively improve the power performance and cycle stability of lithium-ion batteries.

[0065] A fourth aspect of this application also provides a lithium-ion battery, including a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive and negative electrode, wherein the negative electrode is the aforementioned negative electrode provided in this application. The aforementioned negative electrode provided in this application includes the aforementioned silicon-carbon negative electrode material. This silicon-carbon negative electrode material, by constructing a porous silicon-carbon core structure coated with a fluorocarbon layer, achieves a dual improvement in the processing performance and electrochemical performance of the silicon-carbon negative electrode material. It effectively reduces the gas generation of the silicon-carbon negative electrode material during the homogenization process, improves the safety and coating processing performance during the negative electrode production process, and the negative electrode sheet made from it has low interfacial resistance and excellent rate performance. Its application in lithium-ion batteries can effectively improve the rate performance and cycle stability of lithium-ion batteries.

[0066] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.

[0067] Unless otherwise specified, all raw materials and reagents used in the following embodiments of this application are commercially available.

[0068] Example 1

[0069] A silicon-carbon anode material, the preparation method of which specifically includes the following steps:

[0070] (1) 1 kg of phenolic resin-based porous carbon skeleton (D 50 It has a thickness of 8 μm and a specific surface area of ​​1900 m². 2 / g) was placed in a rotary kiln, and 20L of acetylene was introduced at a flow rate of 3L / min; the rotation speed of the rotary kiln was set to 60r / min and the temperature to 550℃, and then a first vapor deposition treatment was performed at this temperature for 6h, so that acetylene was uniformly deposited on the surface and in the pores of the porous carbon framework to form a 2nm thick carbon layer, thus obtaining a composite porous carbon matrix; in this composite porous carbon matrix, the weight ratio of the porous carbon framework to the carbon layer is 100:3;

[0071] (2) Place 1 kg of the composite porous carbon matrix obtained in step (1) in a rotary kiln and introduce 1000 L of silane at a flow rate of 3 L / min; set the rotation speed of the rotary kiln to 60 r / min and the temperature to 500 °C, and then perform a second vapor deposition treatment at this temperature for 12 h, so that the silane is uniformly deposited on the surface and in the pores of the composite porous carbon matrix to obtain the core; wherein, the D of the core 50 It has a diameter of 8 μm and a specific surface area of ​​2.1 m². 2 / g; The weight ratio of the composite porous carbon matrix to the silicon-based material is 1:1;

[0072] (3) Place 1 kg of the core obtained in step (2) in a rotary kiln and introduce 800 L of coating gas at a flow rate of 0.5 L / min. The coating gas includes tetrafluoromethane and acetylene (weight ratio of 1:1). Set the rotation speed of the rotary kiln to 60 r / min and the temperature to 550 °C. Then perform a third vapor deposition treatment at this temperature for 24 h. After completion, maintain the rotation speed and temperature of the rotary kiln and continue to perform heat preservation treatment for 1 h to form a 10 nm thick fluorinated carbon layer on the surface of the core, thus obtaining the silicon-carbon anode material.

[0073] The silicon-carbon anode material prepared in Example 1 (D) 50 It has a diameter of 8 μm and a specific surface area of ​​1.9 m². 2 / g, the carbon content is 48wt%, the silicon content is 48wt%, the fluorine content is 2wt%, and the weight ratio of the core to the fluorinated carbon layer is 100:4.

[0074] The SEM image of the silicon-carbon anode material prepared in Example 1 is shown below. Figure 1 As shown, by Figure 1It can be seen that the silicon-carbon anode material prepared in Example 1 is in the form of irregular particles with relatively uniform particle size and a small number of particle protrusions on the surface.

[0075] Example 2

[0076] The difference from Example 1 is that in step (3), the volume of the encapsulated gas is adjusted to 400L, and the temperature and time of the third vapor deposition process are adjusted so that the weight ratio of the core of the silicon-carbon anode material to the fluorinated carbon layer is 100:0.5 and the thickness of the fluorinated carbon layer is 3nm; the remaining steps are the same as in Example 1.

[0077] Example 3

[0078] The difference from Example 1 is that in step (3), the volume of the encapsulated gas is adjusted to 1000L, and the temperature and time of the third vapor deposition process are adjusted so that the weight ratio of the core of the silicon-carbon anode material to the fluorinated carbon layer is 100:8 and the thickness of the fluorinated carbon layer is 20nm; the remaining steps are the same as in Example 1.

[0079] Example 4

[0080] The difference from Example 1 is that in step (3), the volume of the encapsulated gas is adjusted to 100L, and the temperature and time of the third vapor deposition process are adjusted so that the weight ratio of the core of the silicon-carbon anode material to the fluorinated carbon layer is 100:0.1 and the thickness of the fluorinated carbon layer is 0.5nm; the remaining steps are the same as in Example 1.

[0081] Example 5

[0082] The difference from Example 1 is that in step (3), the amount of fluorine-containing organic compound gas is adjusted so that the fluorine content in the silicon-carbon anode material is 0.2wt%; the remaining steps are the same as in Example 1.

[0083] Example 6

[0084] The difference from Example 1 is that in step (3), the amount of fluorine-containing organic compound gas is adjusted so that the fluorine content in the silicon-carbon anode material is 4wt%; the remaining steps are the same as in Example 1.

[0085] Example 7

[0086] The difference from Example 1 is that in step (3), the amount of fluorine-containing organic compound gas is adjusted so that the fluorine content in the silicon-carbon anode material is 6wt%; the remaining steps are the same as in Example 1.

[0087] Example 8

[0088] The difference from Example 1 is that in step (1), the acetylene injection volume is adjusted to 10L, and the temperature and time of the first vapor deposition process are adjusted so that the weight ratio of the porous carbon skeleton to the carbon layer in the composite porous carbon matrix is ​​100:2 and the thickness of the carbon layer is 1nm; the remaining steps are the same as in Example 1.

[0089] Example 9

[0090] The difference from Example 1 is that in step (1), the acetylene injection volume is adjusted to 50L, and the temperature and time of the first vapor deposition process are adjusted so that the weight ratio of the porous carbon skeleton to the carbon layer in the composite porous carbon matrix is ​​100:5 and the thickness of the carbon layer is 5nm; the remaining steps are the same as in Example 1.

[0091] Example 10

[0092] The difference from Example 1 is that in step (1), the acetylene injection volume is adjusted to 70L, and the temperature and time of the first vapor deposition process are adjusted so that the weight ratio of the porous carbon skeleton to the carbon layer in the composite porous carbon matrix is ​​100:7 and the thickness of the carbon layer is 7nm; the remaining steps are the same as in Example 1.

[0093] Example 11

[0094] The difference from Example 1 is that in step (3), no heat preservation treatment was performed after the third vapor deposition process was completed; the remaining steps are the same as in Example 1.

[0095] Example 12

[0096] The difference from Example 1 is that in step (3), the temperature of the third vapor deposition process is adjusted to 650°C and the time is 48h; the remaining steps are the same as in Example 1.

[0097] Example 13

[0098] The difference from Example 1 is that in step (3), the temperature of the third vapor deposition process is adjusted to 800°C and the time is 12h; the remaining steps are the same as in Example 1.

[0099] Example 14

[0100] The difference from Example 1 is that in step (3), the temperature of the third vapor deposition process is adjusted to 600°C; the remaining steps are the same as in Example 1.

[0101] Example 15

[0102] The difference from Example 1 is that in step (3), the temperature of the third vapor deposition process is adjusted to 900°C; the remaining steps are the same as in Example 1.

[0103] The carbon content, silicon content, and fluorine content, the weight ratio of the core to the fluorinated carbon layer, the thickness of the fluorinated carbon layer, the weight ratio of the porous carbon skeleton to the carbon layer, and the thickness of the carbon layer in the composite porous carbon matrix prepared in Examples 1 to 15 of this application are shown in Table 1.

[0104] The carbon content in the silicon-carbon anode material was determined using a TGA thermogravimetric analyzer; the silicon content was calculated using formula (1): silicon content (wt%) = (m2-m1) / m3×100% (1); where m1 is the weight of the composite porous carbon matrix obtained in step (1), m2 is the weight of the core obtained in step (2), and m3 is the weight of the silicon-carbon anode material; the fluorine content was determined using ion chromatography (IC).

[0105] Table 1

[0106]

[0107] Comparative Example 1

[0108] The difference from Example 1 is that step (3) is omitted, and the core obtained in step (2) is used directly as the silicon-carbon anode material; the remaining steps are the same as in Example 1.

[0109] The silicon-carbon anode material prepared in Comparative Example 1 did not have a fluorinated carbon layer.

[0110] Comparative Example 2

[0111] The difference from Example 1 is that step (1) is omitted, and in step (2), an equal weight of phenolic resin-based porous carbon skeleton is used to replace the composite porous carbon matrix in Example 1; the remaining steps are the same as in Example 1.

[0112] In the silicon-carbon anode material prepared in Comparative Example 2, the core consists of a porous carbon framework and silicon-based material deposited on its surface and in its pores, without the introduction of a carbon layer.

[0113] Comparative Example 3

[0114] A silicon-carbon anode material, the preparation method of which includes the following steps:

[0115] (1) 1 kg of phenolic resin-based porous carbon skeleton (D 50 It has a thickness of 8 μm and a specific surface area of ​​1900 m². 2 / g) was placed in a rotary kiln, and 1000L of silane was introduced at a flow rate of 3L / min; the rotation speed of the rotary kiln was set to 60r / min and the temperature to 500℃, and then vapor deposition was performed at this temperature for 12h to allow silane to be uniformly deposited on the surface and in the pores of the porous carbon material, thus obtaining a silicon-carbon material core; in this silicon-carbon material core, the weight ratio of porous carbon material to silicon-based material is 1:1;

[0116] (2) Place 1 kg of silicon-carbon material core obtained in step (1) in a rotary kiln and introduce 800 L of coating gas at a flow rate of 0.5 L / min. The coating gas includes tetrafluoromethane and acetylene (weight ratio of 1:1). Set the rotation speed of the rotary kiln to 60 r / min and the temperature to 550 °C. Then perform vapor deposition treatment at this temperature for 24 h. After completion, maintain the rotation speed and temperature of the rotary kiln and continue to perform heat preservation treatment for 1 h to form a 10 nm thick fluorocarbon layer on the surface of the silicon-carbon material core to obtain the intermediate product.

[0117] (3) Place 1 kg of the intermediate product obtained in step (2) into a rotary kiln and introduce 20 L of acetylene at a flow rate of 3 L / min; set the rotation speed of the rotary kiln to 60 r / min and the temperature to 550 °C, and then perform vapor deposition treatment at this temperature for 6 h to uniformly deposit the carbon source on the surface and in the pores of the intermediate product to form a 2 nm thick carbon coating layer, thereby obtaining silicon-carbon anode material.

[0118] The silicon-carbon anode material prepared in Comparative Example 3 consists of a silicon-carbon core, a fluorinated carbon layer, and a carbon coating layer from the inside out.

[0119] The gas production of the silicon-carbon anode materials prepared in all the above embodiments and comparative examples of this application was tested. The specific test steps are as follows:

[0120] (1) Preparation of the slurry to be tested: Weigh the negative electrode material, binder (including polyacrylic acid PAA and styrene-butadiene rubber SBR with a weight ratio of 1:1:1:15 to obtain the slurry to be tested; wherein, the negative electrode material is the silicon-carbon negative electrode material prepared in the above-mentioned embodiments and comparative examples of this application respectively.

[0121] (2) Weigh 25g of the slurry to be tested and place it in a sealed bag with a single-sided opening (size 9cm×11cm). Then seal the single-sided opening of the sealed bag with a hot-press sealing machine to obtain the sample to be tested. Weigh the sample to be tested using a density measuring instrument ST300A and record the mass data m0.

[0122] (3) Allow the sample to stand in a sealed environment at 25°C. Weigh the sample using a density meter every 24 hours and record the mass data m. i Repeat 3 times, i=1, 2, 3.

[0123] Calculate the gas production rate according to formula (2). (2), where V is the gas production rate; m0 is the initial weight of the sample to be tested; m i The weight of the sample to be tested is i after standing for i×24h, where i=1, 2, 3; The density of water is 1 g / cm³. 3 .

[0124] Table 2 shows the gas production test data of the silicon-carbon anode materials prepared in all the above embodiments and comparative examples of this application.

[0125] Table 2

[0126]

[0127] It should be noted that in Table 2 above, the 24-hour gas production of the silicon-carbon anode material prepared in Example 1 is 0. This may be because the difference between the weight of the sample to be tested after 24 hours and the initial weight of the sample to be tested is very small, which is lower than the detection limit of the density measuring instrument, resulting in inaccurate measurement and thus the calculated gas production is 0. This shows that the gas production of the silicon-carbon anode material prepared in Example 1 of this application is indeed very small.

[0128] Application Examples

[0129] The lithium-ion battery was assembled according to the following method: (1) Preparation of positive electrode sheet: The positive electrode active material Ni88, conductive agent and binder polyvinylidene fluoride (PVDF) were mixed in a weight ratio of 98:1:1, and then N-methylpyrrolidone (NMP) was added and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry was coated on the surface of a 12μm thick aluminum foil, and then dried at 80°C for 0.5h to obtain a positive electrode sheet with a thickness of 110μm; (2) Preparation of negative electrode sheet: The silicon-carbon negative electrode material (the silicon-carbon negative electrode material prepared by the above-mentioned examples and comparative examples of this application, respectively), graphite, conductive agent and polyacrylic acid (PAA) binder were mixed evenly in a weight ratio of 20:70:2:8, and water was added to obtain a negative electrode slurry; the negative electrode slurry was coated on a 6μm thick aluminum foil. The copper foil surface with a thickness of m was dried at 80°C for 0.5h to obtain a negative electrode sheet with a thickness of 95μm; (3) Lithium-ion battery assembly: Assembly was carried out in a glove box filled with argon gas, using the positive electrode sheet prepared above as the positive electrode and the negative electrode sheet prepared above as the negative electrode; LiPF6, fluoroethylene carbonate (FEC, with a content of 10wt% of the electrolyte) and a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of EC to DEC is 1:1) were mixed to prepare a 1mol / L LiPF6 electrolyte; the separator was a polyethylene separator with double-sided ceramic coating (the thickness of the polyethylene substrate is 7μm and the thickness of the single-sided ceramic coating is 1.5μm); the lithium-ion battery was assembled.

[0130] The following performance tests were performed on the lithium-ion batteries assembled in all the above embodiments and comparative examples: (1) Power performance: Using the Xinwei test cabinet, charge and discharge tests were performed at 25°C with 0.33C and 3C rates in the voltage range of 2.5 to 4.25V. The specific capacity of 0.33C discharge and 3C discharge were measured, and the ratio of 3C discharge specific capacity to 0.33C discharge specific capacity was calculated and recorded as power performance, i.e., power performance (%) = 3C discharge specific capacity / 0.33C discharge specific capacity; (2) Capacity retention rate: 600 cycles were performed at 25°C, 0.33C rate, and voltage range of 2.5 to 4.25V, and the capacity retention rate after 600 cycles was recorded.

[0131] The test results are shown in Table 3.

[0132] Table 3

[0133]

[0134] As can be seen from the above description, the embodiments of this application achieve the following technical effects:

[0135] Comparing Example 1 and Comparative Example 1, it can be seen that, compared with silicon-carbon anode materials without the introduction of a fluorinated carbon layer, the present application provides a fluorinated carbon layer with excellent chemical stability and density on the core surface. On the one hand, it can act as a physical barrier, preventing water molecules from directly contacting silicon; on the other hand, the introduction of fluorine can reduce the surface energy of the fluorinated carbon layer, reduce the wetting and penetration ability of water molecules on the surface of the silicon-carbon anode material, form an effective hydrophobic barrier, and reduce the amount of gas generated during the homogenization process; furthermore, the high electronegativity of fluorine atoms can also improve the electronic structure of the fluorinated carbon layer, reduce the interfacial resistance, provide additional active sites, promote the rapid insertion and extraction of lithium ions, and thus improve the power performance and cycle performance of the prepared lithium-ion battery.

[0136] Comparing Example 1 with Comparative Examples 2 and 3, it can be seen that, compared with silicon-carbon anode materials without a carbon layer (Comparative Example 2), or silicon-carbon anode materials with a carbon layer placed on the outermost side (Comparative Example 3), the carbon layer in this application, placed on the surface of the porous carbon skeleton in the core and within its pores, can effectively reduce the exposed area of ​​silicon-based materials within the pores of the composite porous carbon matrix, thereby reducing the contact path between silicon and water molecules and reducing the amount of gas generated during the homogenization process. At the same time, the porous structure of the composite porous carbon matrix also provides sufficient buffer space for the volume expansion of silicon-based materials during charge-discharge cycles, which can effectively improve the structural stability of silicon-carbon anode materials, thereby improving the power performance and cycle performance of the prepared lithium-ion battery.

[0137] Comparing Examples 1 to 5, and considering the data in Tables 2 and 3, it can be seen that, compared to other ranges, limiting the weight ratio of the silicon-carbon anode material core to the fluorocarbon layer and the thickness of the fluorocarbon layer to the preferred ranges described above in this application is beneficial for the fluorocarbon layer to be more completely and continuously coated on the core surface, better suppressing the side reactions of water molecules and silicon, thereby reducing the gas production of the silicon-carbon anode material during the homogenization process. It is also beneficial for reducing the interfacial resistance of the silicon-carbon anode material, increasing the lithium-ion diffusion rate, and thus improving the power performance and cycle performance of the prepared lithium-ion battery.

[0138] Comparing Examples 1, 5 to 7, and combining the data in Tables 2 and 3, it can be seen that, compared to other ranges, limiting the fluorine content in the silicon-carbon anode material to the preferred range described above in this application is beneficial to improving the hydrophobicity of the fluorinated carbon layer, isolating water molecules from contact with silicon, reducing the gas generation of the silicon-carbon anode material during the homogenization process, and also beneficial to reducing the interfacial resistance of the silicon-carbon anode material, increasing the lithium-ion diffusion rate, and thus improving the power performance and cycle performance of the prepared lithium-ion battery.

[0139] Comparing Examples 1, 8 to 10, and combining the data in Tables 2 and 3, it can be seen that, compared to other ranges, limiting the weight ratio of porous carbon skeleton to carbon layer and the thickness of carbon layer in the composite porous carbon matrix to the above-mentioned preferred range is beneficial to improving the structural stability and interface stability of silicon-carbon anode material, reducing the gas generation of silicon-carbon anode material during homogenization process, and improving the power performance and cycle stability of the prepared lithium-ion battery.

[0140] Comparing Examples 1 and 11, and combining the data in Tables 2 and 3, it can be seen that, compared with other methods, the heat preservation treatment after the third vapor deposition process is beneficial to promote the formation of a more uniform and continuous fluorinated carbon layer, suppress the side reaction between water molecules and silicon, reduce the gas generation of silicon-carbon anode material during homogenization, and also help to reduce the interfacial resistance of silicon-carbon anode material, improve the lithium-ion diffusion rate, and thus improve the power performance and cycle performance of the prepared lithium-ion battery.

[0141] Comparing Examples 1, 12 to 15, and combining the data in Tables 2 and 3, it can be seen that, compared to other ranges, limiting the temperature of the third vapor deposition process to the preferred range described above in this application is beneficial to forming a more uniform and continuous fluorinated carbon layer, reducing the amount of gas generated in the homogenization process of the prepared silicon-carbon anode material, improving its electrochemical performance, and thus improving the power performance and cycle performance of the prepared lithium-ion battery.

[0142] It should be noted that the terms "first," "second," etc., used in the specification and claims of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented, for example, in a sequence other than those described herein.

[0143] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A silicon-carbon anode material, characterized in that, The silicon-carbon anode material includes a core and a fluorinated carbon layer disposed on the surface of the core; the core includes a composite porous carbon matrix and a silicon-based material deposited on the surface and within the pores of the composite porous carbon matrix, the composite porous carbon matrix including a porous carbon skeleton and a carbon layer disposed on the surface and within the pores of the porous carbon skeleton.

2. The silicon-carbon anode material according to claim 1, characterized in that, The silicon-carbon anode material D 50 The size is 4–12 μm; Preferably, in the silicon-carbon anode material, the carbon content is 40-60 wt% and the silicon content is 40-60 wt%. Preferably, the weight ratio of the core to the fluorocarbon layer is 100:(0.4-8).

3. The silicon-carbon anode material according to claim 1 or 2, characterized in that, The thickness of the fluorocarbon layer is 3–20 nm; Preferably, the fluorine content in the fluorinated carbon layer is 0.2 to 4 wt% of the weight of the silicon-carbon anode material.

4. The silicon-carbon anode material according to any one of claims 1 to 3, characterized in that, The kernel's D 50 The size is 4–12 μm; Preferably, the weight ratio of the composite porous carbon matrix to the silicon-based material is 1:(0.67~1.5). Preferably, in the composite porous carbon matrix, the weight ratio of the porous carbon framework to the carbon layer is 100:(2-5). Preferably, the thickness of the carbon layer is 1–5 nm.

5. A method for preparing a silicon-carbon anode material according to any one of claims 1 to 4, characterized in that, The preparation method includes: Step S1: Provide a porous carbon framework, and perform a first vapor deposition treatment on the porous carbon framework in an atmosphere containing a carbon source to obtain a composite porous carbon matrix. Step S2: In an atmosphere containing a silicon source, the composite porous carbon matrix is ​​subjected to a second vapor deposition process to obtain the core. Step S3: In a coating gas atmosphere, the core is subjected to a third vapor deposition process to form a fluorinated carbon layer on the surface of the core, thereby obtaining the silicon-carbon anode material; wherein the coating gas is selected from fluorinated organic compound gas or a combination of fluorinated organic compound gas and alkane gas.

6. The method for preparing the silicon-carbon anode material according to claim 5, characterized in that, In step S3, the ratio of the volume of the encapsulated gas introduced to the weight of the core is (400~1000) L:1kg; Preferably, the coating gas is a combination of fluorinated organic compound gas and alkane gas, and the weight ratio of the fluorinated organic compound gas to the alkane gas is (1-2):(1-2). Preferably, the fluorinated organic compound gas is selected from one or more of tetrafluoromethane, nitrogen trifluoride, Freon, polyvinylidene fluoride, perfluoropolyether, tetrafluoroethylene, trifluorochloroethylene, perfluorocyclobutane, and fluoroethylene carbonate. Preferably, the alkane gas is selected from one or more of C1 to C4 alkane gases; more preferably, the alkane gas is selected from one or more of methane, acetylene, and natural gas. Preferably, the temperature of the third vapor deposition process is 650–800°C, and the time is 12–48 h; more preferably, the temperature of the third vapor deposition process is 750–800°C. Preferably, step S3 further includes a heat preservation treatment performed after the third vapor deposition treatment is completed; more preferably, the temperature of the heat preservation treatment is 650-800°C and the time is 1-2 hours; even more preferably, the temperature of the heat preservation treatment is the same as the temperature of the third vapor deposition treatment.

7. The method for preparing the silicon-carbon anode material according to claim 5, characterized in that, In step S1, the ratio of the volume of the carbon source introduced to the weight of the porous carbon framework is (10-50) L:1kg. Preferably, the carbon source is selected from one or more of methane, acetylene, and natural gas; Preferably, the material used to prepare the porous carbon framework is selected from one or more of resin-based carbon materials, biomass-based carbon materials, and coal-based carbon materials; Preferably, the temperature of the first vapor deposition is 500–600°C, and the time is 2–12 hours.

8. The method for preparing the silicon-carbon anode material according to any one of claims 5 to 7, characterized in that, In step S2, the ratio of the volume of the silicon source introduced to the weight of the composite porous carbon matrix is ​​(500~1000) L:1kg. Preferably, the temperature of the second vapor deposition is 400–600°C, and the time is 8–24 hours.

9. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, characterized in that, The negative electrode active material layer comprises the silicon-carbon negative electrode material according to any one of claims 1 to 4.

10. A lithium-ion battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, characterized in that, The negative electrode is the negative electrode as described in claim 9.